2008
DOI: 10.1016/j.virol.2008.05.036
|View full text |Cite
|
Sign up to set email alerts
|

The nucleoprotein and the viral RNA of infectious salmon anemia virus (ISAV) are localized in the nucleolus of infected cells

Abstract: The infectious salmon anemia virus (ISAV), which belongs to the new genus Isavirus of the Orthomyxoviridae family, is an important pathogen of the salmon farming industry. Indirect immunofluorescence assays carried out with monoclonal antibodies specific for the nucleoprotein (NP) reveal differential staining of sub-cellular compartments in infected cells. Particularly interesting was the staining of the nucleolus, which showed co-localization with nucleolin in CHSE-214, EPC and SHK-1 cells infected with ISAV.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Early studies to define the minimal molecular components for transcription and replication using conventional or modified chloramphenicol acetyltransferase (CAT) reporter assays revealed that the inf A virus promoter functions independently of the rest of the particular genomic segment (9,15,16,36,37,46). In the case of ISAV, critical elements similar to those of inf A virus have been identified in the ISAV transcription/replication cycle, particularly the formation of the panhandle motif in the promoter regions of the genomic segments (28,56) and the importance of the NP (20). Biochemical and biophysical investigation of the transcription/replication cycle of ISAV is still an emerging field, and this report represents the first detailed description of the vRNA and cRNA panhandle RNA secondary structures of an ISAV genomic segment.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies to define the minimal molecular components for transcription and replication using conventional or modified chloramphenicol acetyltransferase (CAT) reporter assays revealed that the inf A virus promoter functions independently of the rest of the particular genomic segment (9,15,16,36,37,46). In the case of ISAV, critical elements similar to those of inf A virus have been identified in the ISAV transcription/replication cycle, particularly the formation of the panhandle motif in the promoter regions of the genomic segments (28,56) and the importance of the NP (20). Biochemical and biophysical investigation of the transcription/replication cycle of ISAV is still an emerging field, and this report represents the first detailed description of the vRNA and cRNA panhandle RNA secondary structures of an ISAV genomic segment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some studies consider nucleolar transit to be of relevance. For example, in the case of orthomyxoviruses there are studies suggesting that prior nucleolar localization is required for the nucleocapsid protein early in replication, which is followed by a combination of nucleoplasmic and nucleolar localizations (12,34). Second, what are the nature and significance of ␦Ag found in the nucleoplasm?…”
Section: Discussionmentioning
confidence: 99%
“…The present study includes examination of the nature and significance of the ␦Ag localization to the nucleolus. Other investigators have noted that for several viruses, specific and essential viral proteins, typically RNA-binding proteins, also locate to the nucleolus, and in some cases such localization only occurs early in infection, leading to the speculation that a "nucleolar transit" may be an essential step in genome replication (12,15). Consistent with but not proof of such a transit for ␦Ag is that during HDV genome replication, the majority of ␦Ag is no longer found in the nucleolus but in the nucleoplasm (4).…”
mentioning
confidence: 99%
“…Cells were then permeabilized for 1 h at room temperature with 0.1% Triton X-100 in 1ϫ PBS. The cells were fixed, and cell sections were blocked with 3% bovine serum albumin (BSA) containing 0.5% Tween 20 for 30 min at 37°C (25). A monoclonal antibody against the ISAV nucleoprotein (clone 2C2/H4; Grupo Bios, BiosChile) diluted 1:500 in 1ϫ PBS and 3% BSA (26) was incubated overnight at 4°C, detected by using a goat anti-mouse antibody conjugated with Alexa Fluor 568 (Life Technologies, USA) diluted 1:1,000 in 1ϫ PBS and 3% BSA, and incubated for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%